DUCT - OISHI YUSUKE; MURAMATSU KEISUKE (2024)
To provide a duct capable of preventing or suppressing generation of dew condensation by a simpler structure or means.SOLUTION: A duct (1, 2) of the present invention have a hollow duct body part (10), at least one through hole (30, 50) that penetrates from an inner wall surface (11) of the duct body part (10) to its outer wall surface (12), and at least one guide part (40, 60) that changes and guides a flow of gas flowing out through the through hole (30, 50).SELECTED DRAWING: Figure 1 【課題】より簡単な構造又は手段で結露の発生を防止又は抑制することが可能なダクトを提供する。【解決手段】本発明のダクト（１，２）は、中空形状のダクト本体部（１０）と、ダクト本体部（１０）の内壁面（１１）から外壁面（１２）に貫通する少なくとも１つの貫通孔（３０，５０）と、貫通孔（３０，５０）を介して流出する気体の流れを変えて案内する少なくとも１つのガイド部（４０，６０）とを有する。【選択図】図１